Assessment of Knowledge, Awareness and Attitude towards Oral Precancer and Cancer among Narikuravar Population in Pondicherry State - Muthanandam, Sivaramakrishnan; Babu, Bontha V.; Muthu, Jananni; Suganya, R.; Vezhavendhan, N.; Kishore, M. (South Asian Journal of Cancer, 2021)
Objective Literature revealed that oral health status and awareness about oral hygiene measures of Narikuravar tribes were very poor. There was also an increased prevalence of tobacco usage among this population. Considering this, incidence and prevalence of oral precancerous and cancerous lesions are expected to be high in this population. Surprisingly, the literature search revealed a lack of data on the awareness, knowledge, and prevalence of oral cancer and precancer in this group. The primary objective of this survey is to assess knowledge, awareness and attitude toward oral precancer and cancer among the Narikuravar tribal population in Pondicherry state.Materials and Methods This questionnaire survey is a part of the Model for Oral Cancer Eradication project conducted among the Narikuravar population in Pondicherry, which is funded by Indian Council of Medical Research (ICMR). A total of 153 participants were recruited for the survey. A prevalidated questionnaire was used for the survey.Results The results indicated that 47% of the participants were aware of what is oral precancer and cancer. As much as 62% knew that chewing tobacco causes oral cancer and 44% thought that the growth of tissue in the mouth could be a sign of oral cancer. Almost 100% did not think that the presence of a red lesion, white lesion, or limitation of mouth opening could be signs of cancer or precancer. Only 16% thought that oral cancer is preventable.Conclusion Awareness about oral cancer and precancer is inadequate among the Narikuravar population of Pondicherry. Majority of the population is not aware of the risks, signs, or treatment options of oral precancer and cancer. The National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases and Stroke (NPCDCS) identified the people’s knowledge gaps, and improving awareness is one of the strategies of the program.
Keywords: Oral cancer; awareness; knowledge; tribal population; Narikuravar tribe